2020
DOI: 10.1002/jmv.26208
|View full text |Cite
|
Sign up to set email alerts
|

The clinical characteristics of pediatric inpatients with SARS‐CoV‐2 infection: A meta‐analysis and systematic review

Abstract: Millions of people were infected with the coronavirus disease 2019 (COVID-19) all over the world. Data on clinical symptoms of pediatric inpatients with COVID-19 infection were unclear. The aim of study was to investigate the clinical features of pediatric inpatients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. PubMed, EMBASE, and the Cochrane Library were searched to seek for studies providing details on pediatric inpatients with SARS-CoV-2 infection which were published from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 34 publications
6
57
1
8
Order By: Relevance
“…We included 18 reviews in our analysis. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Characteristics of the included reviews are shown in table 1; all are freely available online (see online supplemental appendix table 2). All reviews were in English.…”
Section: Resultsmentioning
confidence: 99%
“…We included 18 reviews in our analysis. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Characteristics of the included reviews are shown in table 1; all are freely available online (see online supplemental appendix table 2). All reviews were in English.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of patients had asymptomatic presentation (11/14; 79%) and those with symptoms (3/14; 21%) only showed mild upper respiratory tract infection. It had been shown that asymptomatic SARS-CoV-2 infection is variable and was 17% among household contacts [ 20 ], 17.4% among children in a meta-analysis [ 21 ], and 10% of 100 SARS-COV-2 patients in Taiwan [ 22 ]. In one study, asymptomatic patients were more likely to be present among those <45 years of age but could occur at any age [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, most of the guidelines published so far are more appropriate for adults than for children. Several systematic reviews with simple meta-analysis have been reported, but these have mainly focused on the clinical characteristics of pediatric COVID-19 (5)(6)(7), and data on the transmissibility, rate of viral coinfections, and treatments of pediatric COVID-19 are still lacking. Asymptomatic transmission is the Achilles' heel of COVID-19 pandemic control, as reported by Gandhi et al (8), but the number of asymptomatic infections in children is unknown.…”
Section: Introductionmentioning
confidence: 99%